The European Green Deal: shaping environmentally friendly policies under Article 101 TFEU - Andrea Pezza (Market and Competition Law Review)
In the light of the renewed general interest for environmental issues, resulting from the launch of the European Green Deal by President Von Der Leyen, the paper explores how the EU Commission could promote environmental considerations in the implementation of competition policies. More in detail, starting from the role currently played by environmental factors in the assessment of anticompetitive agreements, the paper will consider whether Article 101 TFEU, as it is formulated – read in the light of the Commission’s decisional practice and of the ECJ’s case law – would support a broader interpretation, according to which the importance of environment-related considerations would be increased, also in line with the expectations of President Von Der Leyen. For this purpose, the present analysis will be focused on the first and third paragraph of Article 101 TFEU, both already used in the past by the Commission – although on the basis of a different legal reasoning – in order to support the relevance of policy considerations (including those environment-related) within competition assessment. The results of such analysis will show that there is sufficient room for a change in the approach of the Commission, that could (and should) be followed also at national level. If such approach will effectively be adopted, the role played by environmental considerations in the implementation of competition policies could be immediately enhanced, without the need to wait for the adoption of a specific legislative act (or, even worse, for a Treaty amendment).